Une durabilité sous conditions ? La production des écoquartiers français, révélatrice d’une doxa néohygiéniste du développement durable - François Valegeas (Métropoles)
This article proposes an analysis of the design assumptions of the French eco-districts, especially through the “social pillar” of these operations embodied by a call for “living together”. This article reveals the normative charge of the combination of devices and accounts on which the implementation of this project is built. The ambition of “living together” in these projects has evolved from being a response to the risks of eco-gentrification to spreading ecological ways of living. The analysis of two specific cases in Rennes and Auxerre shows how this approach of “living together” leads to ecological “living standards”. This empirical work highlights the diversity of practices and the effects that accounts of “living together” produce. Finally, the conception of eco-district reveals a neohygienist doxa of sustainable development based on social standards, moral rules and discourses valuing individual ecological responsibility. Hence, the production of this sustainable city contributes to social relations of domination.